The role of quercetin in the formation of titanium dioxide nanoparticles for nanomedical applications. (March 2023) - Chahardoli, Azam; Jalilian, Fereshteh; Shokoohinia, Yalda; Fattahi, Ali
Abstract: The current work aimed to synthesize and characterize titanium dioxide nanoparticles (TiO2 NPs) using quercetin (QE) and evaluate their biological activities, i.e., anti-hemolytic, anti-inflammatory, and cytotoxicity effects. The crystallographic phase and morphology of biosynthesized QE-TiO2 NPs were characterized by XRD (X-Ray Diffraction) and TEM/FE-SEM (Transmission/Field-Emission Scanning Electron Microscopy) micrographs. Functional groups involved in the synthesis process were determined by FTIR spectroscopy (Fourier Transform-Infrared Spectroscopy). Based on the characterization results, selected QE-TiO2 NPs showed a rutile phase, spherical shape, and a size range of 7.3–39 nm. The QE-TiO2 NPs did not show a hemolytic effect. They indicated 95.3% red blood cells (RBCs) membrane stabilization activity and 82.6% inhibition of bovine serum albumin (BSA) denaturation, similar to a standard drug, which proved their anti-inflammatory effects. The attained results from cytotoxicity studies revealed the toxic effects of QE-TiO2 NPs with IC50 values below 100 and 50 μg/mL for human breast cancer cells of MCF-7 and melanoma cancer cells of A375, respectively. These NPs did not significantly affect normal skin fibroblast cells up to 50 μg/mL and only showed a 16% inhibition rate on the cell viability at 100 μg/mL. These NPs also induced excessive ROS generation. This work established the blood/biocompatibility and excellent nanomedical applications of biosynthesized QE-TiO2 NPs. Highlights: The biosynthesized TiO2 NPs using quercetin (QE- TiO2 NPs) with spherical shape and size range of 7.3-39 nm showed a rutile crystallographic phase. Rutile QE- TiO2 NPs decreased the viability of MCF-7 and A375 cancer cells with IC50 values below 100 and 50 μg/mL, respectively. The biosynthesized QE- TiO2 NPs did not show hemolytic effects on RBCs. QE- TiO2 NPs showed excellent membrane stabilization activity and anti-inflammatory potential similar to that of the reference drug.